IMPLIKASI MEDIA MASSA TERHADAP PERAN GENERASI Z DAN MILENIAL DALAM MENDORONG PERTUMBUHAN EKONOMI HIJAU - Artana, Nengah Yudik; Yasa, I Komang Widya Purnama; Dharma Yanti, Ni Wayan Alinda (Waisya : Jurnal Ekonomi Hindu, 2025)
Government policy regarding the green economy (environmentally friendly concept), mass media also plays a role in inspiring the younger generation to innovate in creating sustainable solutions. This research will examine how mass media can shape the views of generation Z and millennials about the importance of the green economy in the context of Indonesia Emas 2045, mass media can motivate generation Z and millennials, mass media representation of the perceptions of Generation Z and Millennials and the creation of a sustainable ecosystem into economic policy. This research uses descriptive qualitative methods with data collection techniques in the form of non-participant observation, semi-structured interviews, and documentation analysis. Research location is Mataram City Mass Media with a focus on Suara NTB, Lombok Post and Radar Lombok. Informant selection technique with purposive sampling. This research also uses the News Factory Model and Audience Reception Theory approaches. The results of this study state that the implications of mass media on the role of generation Z and millennials are very significant, this is because the news that is carried out continuously (intensely) can increase the awareness of Generation Z and Millennials of renewable energy, natural sustainability and green economy towards Indonesia Emas 2045. This is supported by the participation of Generation Z and Millennials in social activities carried out by the mass media.